Inprecor : . Inprecor : correspondance de presse internationale
(1974) - (1976) subtitled: Correspondance de presse internationale. - Engl.ed.: Inprecor (ZK 38640). - German ed.: Inprekorr (ZK 40374). - Spanish ed.: Inprecor (ZK 38641). - For suppl. see: Inprekor. Miedzynarodowa koorespondencja prasowa.